Carbohydrate intake and food sources of junior triathletes during a moderate and an intensive training period - Carlsohn, A.; Nippe, S.; Heydenreich, J.; Mayer, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
The study was conducted to investigate the quantity and the main food sources of carbohydrate (CHO) intake of junior elite triathletes during a short-term moderate (MOD; 12 km swimming, 100 km cycling, 30 km running per wk) and intensive training period (INT; 23 km swimming, 200 km cycling, 45 km running per wk). Self-reported dietary-intake data accompanied by training protocols of 7 male triathletes (18.1 ± 2.4 yr, 20.9 ± 1.4 kg/m2) were collected on 7 consecutive days during both training periods in the same competitive season. Total energy and CHO intake were calculated based on the German Food Database. A paired t test was applied to test for differences between the training phases (? = .05). CHO intake was slightly higher in INT than in MOD (9.0 ± 1.6 g · kg-1 · d-1 vs. 7.8 ± 1.6 g · kg-1 · d-1; p = .041). Additional CHO in INT was mainly ingested during breakfast (115 ± 37 g in MOD vs. 175 ± 23 g in INT; p = .002) and provided by beverages (280.5 ± 97.3 g/d vs. 174.0 ± 58.3 g/d CHO; p = .112). Altogether, main meals provided approximately two thirds of the total CHO intake. Pre- and postexercise snacks additionally supplied remarkable amounts of CHO (198.3 ± 84.3 g/d in INT vs. 185.9 ± 112 g/d CHO in MOD; p = .231). In conclusion, male German junior triathletes consume CHO in amounts currently recommended for endurance athletes during moderate to intensive training periods. Main meals provide the majority of CHO and should therefore not be skipped. CHO-containing beverages, as well as pre- and postexercise snacks, may provide a substantial amount of CHO intake in training periods with high CHO requirements.